Village Government Performance and Public Service Quality: An Islamic Economic Perspective in Bagelen Village, Lampung - Putri, Meri Sintia (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2024)
The Bagelen Village government, as an extension of the district government, is responsible for providing the best possible services to the community to achieve overall welfare in accordance with relevant laws and regulations. However, Bagelen Village faces several issues, such as annual floods and complaints about the unequal distribution of social assistance. This study aims to analyze community satisfaction with service quality and the performance of the Bagelen Village government from an Islamic economic perspective. This qualitative research employs field research and literature review methods. Data was collected through observation, interviews, and documentation and analyzed using SWOT analysis to assess the government's position based on strengths, weaknesses, opportunities, and threats. The findings indicate that the performance of the Bagelen Village government is satisfactory to the community, with a focus on welfare through infrastructure development, administrative services, and fair distribution of social assistance. The performance aligns with the Islamic economic perspective in the Qur'an and Sunnah, aiming to reduce socio-economic inequalities in the village.